Generation mean analysis of pearl millet [Pennisetum glaucum (L.) R. Br.] grain iron and zinc contents and agronomic traits in West Africa. (November 2020) - Boubacar Gaoh, Bassirou Sani; Gangashetty, Prakash I.; Mohammed, Riyazaddin; Dzidzienyo, Daniel Kwadjo; Tongoona, Pangirayi
Abstract: Pearl millet is the most important staple food crop for millions of people across the world. Micronutrient malnutrition is the major problem for people living in the semi-arid regions of Africa. Identification of gene effects controlling the inheritance of grain Fe and Zn will be helpful in formulating suitable breeding strategies for biofortified pearl millet development. Hence, generation mean analysis was used to study epistasis and estimate gene effects for grain iron and zinc contents along with the agronomic and morphological traits. Six generations P1, P2, F1, F2, BC1 P1 and BC1 P2 were generated and were evaluated during the 2018–19 off season. Analysis of variance showed significant variability for all the traits in both generations. Six parameter model revealed predominance of additive gene effects for inheritance of grain iron concentration, and additive × additive type of non-allelic interactions. For grain zinc concentration additive gene effects were preponderant compared to non-additive gene effects, and only additive × dominance gene effects were significant among the three types of epistasis. Grain weight per plant was predominantly under non-additive gene effects and additive × additive and additive × dominance gene effects type of epistasis was detected in each cross. Likewise, for flowering non-additive gene effects were most important with the presence of dominance × dominance type of epistasis. For plant height, panicle circumference and length, additive × additive genes effects were the most important among the three type of non-allelic gene action.These findings can be helpful in enehancing the pearl millet breeding programs in Africa. Graphical abstract: Crossing mechanism of pearl millet [ Pennisetum glaucum (L.) R. Br.] genotypes for generation means study and genetic inheritance of grain Fe and Zn contents, agronomicand morphological traits. Image 1 Highlights: Additive gene action was predominant over dominant gene action for Grain iron. Additive x dominance gene effects were significant for grain Zinc density. Preponderance of non-additive gene action in the inheritance of days to flowering. Dominance x dominance gene action was significant for days to flowering. Plant height, panicle length and girth shown additive x additive gene effects.